Pengaruh Social Media Marketing Dan Online Customer Review Serta E-WoM Terhadap Online Impulsive Buying Pada Produk Skintific Clay Stick Di E-Commerce Tiktok Shop (Studi Pada Pengguna Produk Skintific Clay Stick Di Kota Samarinda) - Dian Yuniardi; Fareis Athalets (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the influence of Social Media Marketing, Online Customer Reviews, and Electronic Word of Mouth on Online Impulsive Buying of Skintific Clay Stick products at the E-Commerce TikTok Shop in Samarinda City. The method used in this research was a purposive sampling technique with a sample size of 100 respondents. The data sources used are primary and secondary data which focus on quantitative data types. The data analysis techniques carried out in this research used research instrument data tests, classical assumption tests, statistical tests and hypothesis tests. The results of this research show that: Social Media Marketing has a positive and significant effect on Online Impulsive Buying, Online Customer Reviews has a negative and significant effect on Online Impulsive Buying, and Electronic Word of Mouth has a positive and significant effect on Online Impulsive Buying.